Computationally Efficient Fluid-Particle Dynamics Simulations of Arterial Systems (Communications in Computational Physics, 2020)
Realistic and accurate computer simulations of the particle-hemodynamicsin arterial systems can be a valuable tool for numerous biomedical applications. Examplesinclude optimal by-pass grafting and optimal drug-delivery, as well as bestmedical management concerning the cardio-vascular system. However, such numericalanalyses require large computer resources which may become prohibitive for extendedsets of arterial bifurcations. A remedy is to develop a hybrid model where thefirst few generations of the bifurcating arteries of interest are simulated in full 3-D,while a 1-D model is then coupled for subsequent bifurcations. Alternatively, a 1-Dcomputer model can be directly employed to simulate fluid-particle transport in complexbifurcating networks.Relying on a representative axial velocity profile, a physiological 1-D model hasbeen developed and validated, which is capable of predicting with reasonable accuracyarterial flow, pressure field and elastic wall interaction as well as particle transport.The usefulness of the novel 1-D simulation approach is demonstrated via a comparisonto 3-D blood flow and microsphere transport in a hepatic artery system, featuringas outlets one major branch and four small daughter vessels. Compared to the3-D simulation, the 1-D analysis requires only about 1% of computational time. Thehybrid modeling approach would be also applicable to the human respiratory tract toevaluate the fate of inhaled aerosols.A simple and cost-effective way to simulate particle-hemodynamics is using a 1-Dmodel for simulating arterial pressures and flow rates as well as microsphere transport,based on assumptions involving the use of a simple algebraic pressure-area relation, anexponential elasticity model for the vessels, and considering only unidirectional flowwith a representative skewed velocity profile. In summary, the novel contributions are:• Particle tracking in arteries via 1-D fluid modeling and selection of an averaged,skewed velocity profile based on 3-D simulation results to provide more realistic friction and inertia term values for modeling a flow system with bifurcations. • The 1-D model can be coupled to a 3-D model so that simulations can be run forlarger regions of vascular or lung-airway systems.